The elderly’s religious observances provisions in Islamic jurisprudence - Amir Al-Rubaie, Raghad Mahdi Abdul (Opción, 2020)
The study aims to investigate the elderly’s religious observances provisions in Islamic jurisprudence via comparative qualitative research methods. As a result, there is no deference opinion among the scholars about ablation conditions, including the full brain witch is the asset of trust so fasting is not an obligation for mad. In conclusion, Islam is the religion of tolerance, holding, flexibility, and balance as it obligate Muslim to perform his duties, on the other hand, it gave him some license to match with the possibility and nature of human.